Otolaryngology in the medical school curriculum: Current trends in the United States. (14th June 2016) - Boscoe, Elizabeth F.; Cabrera‐Muffly, Cristina
Abstract : Objectives/Hypothesis: To identify trends in medical school otolaryngology curriculum requirements. Study Design: Survey of United States allopathic medical schools. Methods: A survey was sent to deans of curriculum at allopathic medical schools. We identified opportunities for medical students to learn basic concepts in otolaryngology during their undergraduate medical training. The opportunities were classified into preclinical and clinical as well as elective and mandatory rotations. Results: Of the schools surveyed, 60% responded. Mean class size was 149 students. Sixty‐eight percent of surveyed schools noted that 75% to 100% of their students participated in preclinical otolaryngology experiences, with 59% reporting a mandatory preclinical otolaryngology module for all students. Eighty‐nine percent of schools offered otolaryngology as a clinical elective rotation, with a mean of 12 students participating yearly. Only 7% of schools required a mandatory otolaryngology clinical rotation. Conclusion: Our data suggest that medical students do not receive sufficient exposure to otolaryngology during medical school. Increased requirements for otolaryngology curriculum may be beneficial to all medical students, regardless of their specialty choice. Level of Evidence: NA. Laryngoscope, 00:000–000, 2016 127:346–348, 2017